Analisis dan Perancangan Website Sebagai Sarana Informasi Pada Lembaga Bahasa Kewirausahaan Dan Komputer AKMI BATURAJA Menggunakan PHP dan MySQL - Yunita trimarsiah; Muhajir Arafat (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
Language Institute of entrepreneurship and the computer is part of AKMI AMIK Baturaja which has a mission to carry out training activities English language skills and computer applications as needed workforce. However, in promoting the activities of the institution still using a manual system that is by sticking a brochure of activities in the announcement that has been provided, therefore to be able to provide information and promote activities organized by the Institute of Language entrepreneurship and Computers necessary means in the form of a website to be designed using PHP and Mysql. With the existence of the website is expected the public more familiar with the Language Institute of Entrepreneurship and Computers, and the agency can also add a promotional tool for any activity through the website, but it is also for people who want to register for activities LBKK can register online without the need to come directly to AKMI Baturaja.